Comparison of sporadic and familial disease amongst 580 cases of motor neuron disease. - Li, T M (1988)
A review of 580 hospital case notes of patients with motor neuron disease (MND) revealed 20 families in which more than one case had been reported. For 27 of the cases in these families full medical records were available, and a history of a further 37 affected family members were obtained. The cases in these 20 families are termed familial and the remainder sporadic. Parent to child transmission occurred in 16 of the 20 families of the familial cases, suggesting autosomal dominant inheritance. In three families there was involvement of siblings only, and in one family two cousins were affected. The sex ratio for the documented familial case records seen was 0.8:1 (M/F = 12:15), for the total (documented and historical) it was 1.06:1 (33:31), but in sporadic cases it was 1.6:1 (341:212) and more frequent occurrence of sensory features at presentation was reported in the familial cases (15% in the familial cases and 5% in the sporadic cases). However, none of these differences reached statistical significance. Familial cases also differed from sporadic cases in having a younger age of onset (a mean of 52 years in the familial cases compared with 56 years in the sporadic) and in the shorter median reported duration of illness (1.1 year in the familial cases; 2.6 years in the sporadic). However, in only one fifth of sporadic cases was the age at onset and death known, although this was known for 22 of the 27 familial cases, so that the data on survival and age of onset are too incomplete to test formally.